Mannose metabolism is required for mycobacterial growth - Patterson, John H; Waller, Ross F; Jeevarajah, Dharshini; Billman-Jacobe, Helen; McConville, Malcolm J (Biochemical journal, 2003)
Mycobacteria are the causative agents of tuberculosis and several other significant diseases in humans. All species of mycobacteria synthesize abundant cell-wall mannolipids (phosphatidylinositol mannosides, lipoarabinomannan), a cytoplasmic methylmannose polysaccharide and O-mannosylated glycoproteins. To investigate whether these molecules are essential for mycobacterial growth, we have generated a Mycobacterium smegmatis mannose auxotroph by targeted deletion of the gene encoding phosphomannose isomerase (PMI). The PMI deletion mutant displayed a mild hyperseptation phenotype, but grew normally in media containing an exogenous source of mannose. When this mutant was suspended in media without mannose, ongoing synthesis of both the mannolipids and methylmannose polysaccharides was halted and the hyperseptation phenotype became more pronounced. These changes preceded a dramatic loss of viability after 10 h in mannose-free media. Mannose starvation did not lead to detectable changes in cell-wall ultrastructure or permeability to hydrophobic drugs, or to changes in the rate of biosynthesis of other plasma-membrane or wall-associated phospholipids. These results show that mannose metabolism is required for growth of M. smegmatis and that one or more mannose-containing molecules may play a role in regulating septation and cell division in these bacteria.